Model based on improved competitiveness indicator critical to management in small companies service offters mointenance of cacheters heavy - García Zapata, Teonila (2013)
This investigation seeks to increase the competitiveness of small companies that provide maintenance services for heavy equipment by designing game del based on indicators derived from the critical processes of this service, that is, those chain processes value, leading to greater competitive ness for the company. With what is expected to help raise the competitiveness of companies in this sector and encourage research to develop tools or more sophisticated models that will help little by little, the management of MSE (98% of Peruvian companies), improving the competitiveness country’s business sector.